2017
DOI: 10.23917/reaksi.v2i2.4894
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2011-2015)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 2 publications
1
12
1
19
Order By: Relevance
“…The results of this study are in line with the research of Pujiasih (2013), who showed that environmental performance influencedCSR when the company's efforts to create a positive environment were measured through the PROPER program, and so had a positive influence on CSR disclosure by the company. But it is not in line with the research conducted by Sukasih and Eko (2017), who stated that environmental performance does not affect CSR.…”
Section: Effect Of Environmental Performance On Corporate Social Respcontrasting
confidence: 61%
“…The results of this study are in line with the research of Pujiasih (2013), who showed that environmental performance influencedCSR when the company's efforts to create a positive environment were measured through the PROPER program, and so had a positive influence on CSR disclosure by the company. But it is not in line with the research conducted by Sukasih and Eko (2017), who stated that environmental performance does not affect CSR.…”
Section: Effect Of Environmental Performance On Corporate Social Respcontrasting
confidence: 61%
“…That means board size, independent commissioner and the age of the commissioner board partially did not affect the corporate social responsibility disclosure and thus H 1 , H 2 , and H 3 were rejected. The size of the board does not affect the corporate social responsibility disclosure according to Sukasih & Sugiyanto (2017) because the small amount makes the supervision of the board of management and directors less effective so that it fails to put pressure on managers and directors to disclose wider information including about responsibility social enterprise in order to reduce information asymmetry. This is shown in the results of the descriptive analysis where the number of commissioners owned by the company which is the research sample is only 6 people.…”
Section: Resultsmentioning
confidence: 99%
“…Konflik yang timbul juga bisa dikarenakan adanaya ketidakseimbangan sebuah informasi yang dimiliki oleh agent dan principal atau biasanya yang disebut dengan astimetri informasi. Dari ketidakseimbangan informasi yang ada dapat memberikan kesempatan kepada manajer untuk melakukan suatu tindakan opportunitis seperti halnya manajemen laba (Sukasih dan Sugianto, 2017).…”
Section: Tinjauan Literatur Dan Pengembangan Hipotesis Teori Keagenanunclassified
“…Untuk menghitung CSRI menggunakan pendakatan dikotomi dan nilai 1 jika diungkap. Selanjutnya skor dari setiap item akan dijumlahkan guna memperoleh keseluruhan skor dari setiap perusahaan (Sukasih dan Sugianto, 2017).…”
Section: Definisi Operasional Variabel Dan Pengukurannya Pengungkapanunclassified
See 1 more Smart Citation